THE PROBABILITY OF CHANGING THE VOLUME OF VARIOUS TYPES OF MEMORY IN YOUNG PEOPLE AFTER TOOTH EXTRACTION - Shundryk, M.A.; Marchenko, I.Y.; Tkachenko, I.M.; Brailko, N.M.; Marchenko, V.Y. (World of Medicine and Biology, 2023)
In this work, a study of the volume of different types of memory in young people after tooth extraction for orthodontic indications and as a result of untimely caries treatment was carried out. Loss of teeth leads to deterioration of the chewing process, which improves blood supply to certain brain areas, including the hippocampus. In the process of chewing food, stimulating sensory impulses enter the hippocampus, whose function is to remember and encode the environment and spatial memory. Reducing the number of teeth reduces the level of such stimulation. Extraction of teeth at an early age also causes chronic stress that affects interpersonal interaction, which may later contribute to the impairment of some cognitive functions, particularly memory.